Alternative mechanisms of managing the education’s development in the social investment model of Russia’s economic growth: standardization versus deregulation - Dianova, Valentina Yu; Krasilnikova, Varvara G.; Kelina, Kirena G.; Nazarenko, Anton V. (Frontiers in Education, 2023)
Regression analysis is used to determine the contribution of the factors of managing the development of higher education – share of university branches – to increase the population’s quality of life. To determine the optimal approach to managing education’s development in the social investment model of Russia’s economic growth with alternative mechanisms of standardization and deregulation. The results of the research show that absolute standardization, as well as absolute deregulation of higher education, does not allow achieving significant results in the sphere of increase in quality of life in Russia. The determined and substantiated optimal scenario of managing the development of higher education in Russia to increase the quality of life envisages a foundation on a flexible approach, which envisages the combination of standardization and deregulation. It is recommended to entirely refuse branches in favor of main universities, refuse government financing in favor of fee-based education and refuse diversification of education forms in favor of the intramural form of study. This allows raising the quality of life by 13.26% (up to 70.87 points). For practical implementation of this approach, it is offered to allow each region to form their own programs of development of higher education with the foundation of the main federal principles.